Game management under ranching and farming condition in the Czech Republic and Europe - Kotrba, Radim (Maugli), author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Seasonal breeding of indigenous game species in fenced areas was documented from Upper Paleolithic time in some parts of Europe known as winter foddering of red deer, but expansion of fenced hunting game parks, where game was permanently present, has become widespread from Middle Ages. Nowadays, we can recognise in some countries of Europe two type of breeding of fenced game, extensive called as deer/game parks or estates and intensive game farms with majority of deer farms. The deer farming as industry in Europe is recognised from early seventies last century in the most countries even some small hobby breeders has been always present. In general, game kept in parks and estates serve mainly for conservation of species and habitats and of course for trophy hunting. On the contrary deer is bred in farms mainly for meat production because of stable and controlled quality and for live sales because of outstanding quality. Nevertheless, we can recognise broad diversity of approaches based on game historical use, legislation and also environmental condition across Europe. Therefore, game is broadly considered and managed as wild under extensive fenced system and as domestic livestock with some exemptions on game farms. Historically, game in fenced areas owned by nobility helped to preserve indigenous species, but very often was also as place for introduction of exotics. Recently to release exotic species in wild or to keep them in game parks is prohibited by legal conditions in most countries, but usually permitted in farms. To recognise, what is exotic species is usually based on historical presence. Therefore, some ungulates originated in Asia or North America introduced one or more hundred years ago to game park, which established local populations in wild after escape, become hunted game in wild and in fenced areas as well and generally accepted. Talk will overview game management approaches, problems and challenges in Europe based on hunter's and/or meat producer's perspective frame it in conservation effect and giving examples not only from the Czech Republic.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.